2017
DOI: 10.1126/science.aam8526
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a mammalian circular RNA locus causes miRNA deregulation and affects brain function

Abstract: Hundreds of circular RNAs (circRNAs) are highly abundant in the mammalian brain, often with conserved expression. Here we show that the circRNA Cdr1as is massively bound by the microRNAs (miRNAs) miR-7 and miR-671 in human and mouse brains. When the locus was removed from the mouse genome, knockout animals displayed impaired sensorimotor gating-a deficit in the ability to filter out unnecessary information-which is associated with neuropsychiatric disorders. Electrophysiological recordings revealed dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
936
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,003 publications
(1,027 citation statements)
references
References 65 publications
(72 reference statements)
35
936
0
5
Order By: Relevance
“…CircRNAs are usually formed by noncannonical splice reactions and reside in the cytoplasm where one circRNA, CDR1AS, regulates miR-7 stability and transport in neurons (Piwecka, et al 2017). …”
Section: Page 3 Of 53mentioning
confidence: 99%
“…CircRNAs are usually formed by noncannonical splice reactions and reside in the cytoplasm where one circRNA, CDR1AS, regulates miR-7 stability and transport in neurons (Piwecka, et al 2017). …”
Section: Page 3 Of 53mentioning
confidence: 99%
“…Inhibitory actions between two species i and j are assumed to follow mass-action 46 kinetics (see [24] for a reference), with rate constant k ij for (i, j) ∈ {(C, M ), (M, F )} in 47 the case of miRNA sponge repressing miRNA and miRNA repressing transcription 48 factor mRNA, respectively.…”
mentioning
confidence: 99%
“…Based on our analysis, circRNA in this network 175 motif acting as a miRNA sponge will push the steady state closer to oscillatory 176 behaviour, potentially crucial to the maintenance of this state. In the same vein, recent 177 work involving circRNA characterisation has shown, through knockdown experiments, 178 that specific circRNA are heavily involved in neurogenesis, a process where such 179 oscillatory behaviour is likely crucial [47,48].…”
mentioning
confidence: 99%
“…Rajewsky and colleagues, in collaboration with the Birchmeier lab, recently published results from a Cdr1as knockout (KO) mouse model in Science [10]. To date, this is the first and only KO model of a circRNA, and the first full deletion of a circRNA transcript involved in ceRNA crosstalk.…”
mentioning
confidence: 99%
“…Cdr1as KO mice are viable and fertile without gross abnormality. However, Piwecka et al [10] observed that these mice suffer from defects in sensorimotor gating, possibly due to altered excitatory synaptic transmission in the absence of Cdr1as. The direct interaction between Cdr1as and both miR-7 and miR-671 was confirmed in vivo by a modified CLIP assay in which miRNAs that coprecipitate with AGO2 are ligated to their RNA target sites and the chimeric RNAs can be sequenced.…”
mentioning
confidence: 99%